Cardiac magnetic resonance in cardiac resynchronization therapy - How useful it can be - Zdravkovic, Marija; Popadic, Viseslav; Klasnja, Slobodan (Halo 194 Scientific Journal of Emergency Medicine, 2020)
Patients with heart failure, reduced ejection fraction, and signs of myocardial dyssynchrony have a poor prognosis. Cardiac resynchronization therapy is a proven therapeutic modality that improves symptoms of heart failure and reduces morbidity and mortality in these patients. Better identification of patients who could respond to cardiac resynchronization therapy is an important aspect. Cardiac magnetic resonance is a useful, non-invasive, sophisticated diagnostic tool that can provide useful information on the etiology of heart failure, and the severity of mechanical dyssynchrony of the left ventricle. It is helpful in evaluating the myocardial scar burden and in the optimal positioning of the LV lead to improve clinical outcomes. Significant clinical benefit has also been proven in following the patients after CRT implantation.